Determination of Epiphyseal Union Age in the Knee and Hand Joints Bones among the Saudi Population in Taif City - Majed O. Aljuaid; Osama R. El-Ghamry (Radiology Research and Practice)
Introduction. The use of radiographic data for determination of age, according to the epiphyseal union stage, is a widely accepted method and considered scientifically approved. The aim of the present work is to estimate the age of epiphyseal union of hand and knee joints bones among Saudi population in Taif City. Subjects and Method. A retrospective cross-sectional study was conducted in the Armed Forces Hospitals (4 hospitals) in Taif City. The five-stage method was used for the union assessment. Results. A total of 473 patients’ X-ray images were involved. Approximately three-quarters of the knee and hand images were males’ images (77.25% and 75.41%, resp.). The means of age of stage 3 (age of recent union) in the knee joint were 23.63 ± 3.12 and 21.19 ± 3.41 in males and females, respectively, and 19.84 ± 3.47 and 17.19 ± 1.61 in hand joints for males and females, respectively. There were significant differences between males and females in the means of age for stages 1, 3, and 4 at the knee joint plates and for stages 0, 2, and 3 in the hand joint plates (P values were <0.05). However, by comparing the mean of age for each stage with the previous stage mean in males and females, there was a significant difference between stages 0–4 (P values ≤ 0.0001, ≤0.001, <0.0001, and <0.001, resp.) and stages 2 and 3 (P value = 0.012) in knee joint images for males and females, respectively. In addition, there were significant differences between stages 2–4 in hand joints for males and females (P values ≤ 0.0001, <0.0001, <0.0001, and <0.0001, resp.) and stages 0 and 1 for males only (P value = 0.002). Conclusion and Recommendation. This study suggests that the union of epiphyses of knees and hands in Taif City occurs later than other places. More studies must be done with female samples.